A call for a CALL Post lockdown online learning at King Khalid University: Students’ Perspective - Khan, Dr.Aayesha Sagir; Alnmer, Ms Samar (The journal of contemporary issues in business and government, 2021)
The aim of the study is to examine the opportunities and challenges of remote emergency learning with emphasis on language learning during COVID-19. Technology has assumed an even larger role in the education of our students amid a global pandemic. This is an unprecedented time where the universities around the world embraced online learning as the new normal. The research mainly investigates the learner’s views and perceptions of online learning, as well as its future potential in higher education and the impact of online learning on language learners. The study's emphasis on Blackboard (BB) stems from the fact that it is a widely used teaching and learning medium at many Saudi and foreign universities. For the same quantitative survey was done on the 226 students at King Khalid University undergraduate students. The findings also suggest that in times of lockdowns and social distancing due to COVID-19 pandemic, online learning which was obligatory was welcomed by students. The interview conducted with the respondents reveled that the direct contact with the professors was one of the motivational factors for them. In addition to tools, the findings reveal that faculty preparation, student accessibility, and motivation all play a role in ICT integrated learning.